Increased Severe Cases and New-Onset Type 1 Diabetes Among Children Presenting With Diabetic Ketoacidosis During First Year of COVID-19 Pandemic in Turkey - Kiral, Eylem; Kirel, Birgul; Havan, Merve; Keskin, Mehmet; Karaoglan, Murat; Yildirim, Ahmet; Kangin, Murat; Talay, Mehmet Nur; Urun, Tuba; Altug, Umit; Kesici, Selman; Tufan, Erennur; et al. (Frontiers in Pediatrics, 2022)
Introduction: There have been some significant changes regarding healthcare utilization during COVID-19 pandemic. Majority of the reports about the impact of the COVID-19 pandemic on diabetes care, are from the first wave of the pandemic. We aim to evaluate the potential effects of the COVID-19 pandemic on the severity of diabetic ketoacidosis (DKA) and new onset Type 1 diabetes presenting with DKA, and also evaluate children with DKA and acute COVID-19 infection. Methods: This is a retrospective multi-center study among 997 children and adolescents with type 1 diabetes who were admitted with DKA to 27 pediatric intensive care units in Turkey between first year of pandemic and pre-pandemic year. Results: The percentage of children with new-onset Type 1 diabetes presenting with DKA was higher during the COVID-19 pandemic (p<0.0001).The incidence of severe DKA was also higher during the COVID-19 pandemic (p<0.0001) and also higher among children with new onset Type 1 diabetes (p<0.0001). HbA1c levels, duration of insulin infusion, and length of PICU stay were significantly higher/longer during the pandemic period. Eleven patients tested positive for SARS-CoV-2, eight were positive for new onset Type 1 diabetes, and nine tested positive for severe DKA at admission. Discussion: The frequency of new onset of Type 1 diabetes and severe cases among children with DKA during the first year of the COVID-19 pandemic. Furthermore, the cause of the increased severe presentation might be related to restrictions related to the pandemic; however, need to evaluate the potential effects of SARS-CoV-2 on the increased percentage of new onset Type 1 diabetes.